Effective treatment of hypertension by recombinant Lactobacillus plantarum expressing angiotensin converting enzyme inhibitory peptide - Guilian Yang; Yanlong Jiang; Wentao Yang; Fang Du; Yunbao Yao; Chunwei Shi; Chunfeng Wang (2015)
Hypertension is considered the most serious risk factor for cardiovascular disease. Angiotensin-converting enzyme inhibitory peptides (ACEIPs), which are made from tuna frame protein (TFP) and yellow fin sole frame protein (YFP), have been used previously to treat hypertension. However, the production of these short peptides is usually dependent on enzymatic hydrolysis, resulting in a digested mixture that makes it difficult to purify the ACEIPs. Although it has been reported that ACEIPs could be produced in recombinant Escherichia coli strains, the use of lactic acid bacteria in the production of ACEIPs has not been demonstrated.In this study, the ACEIP coding sequences from TFP and YFP were joined through an arginine linker and expressed in the Lactobacillus plantarum (Lb. plantarum) NC8 strain by an inducible vector pSIP-409. Then, the antihypertensive effects were determined in the model of spontaneously hypertensive rats (SHRs) by measuring the blood pressure, hematology, blood biochemistry and nitric oxide (NO), endothelin (ET) and angiotensin II (Ang II) levels. The results showed that oral administration of recombinant Lb. plantarum NC8 (RLP) significantly decreased systolic blood pressure (P < 0.01) during treatment, which lasted for at least 10 days after the last dose. Furthermore, the presence of RLP resulted in an increased level of NO, as well as decreased levels of ET and Ang II in plasma, heart, and kidney. In addition, a dramatically decreased triglyceride level was also observed even though there was no significant change in hematology or blood biochemistry. Although some drawbacks were still observed, such as the presence of an antibiotic selection marker, no obvious side effects or bacterial translocation were observed in vivo, indicating the potential application of RLP in the treatment of hypertension.These results demonstrated the effectiveness and safety of RLP on the treatment of hypertension.